Anti-arbitration injunctions: walking the tightrope. (1st May 2020) - Garnett, Richard
Abstract: Anti-arbitration injunctions are a controversial issue in the field of international arbitration. While some commentators decry them as an interference with the autonomy and independence of arbitrators, English and other common law courts steadfastly refuse to renounce them entirely. By reference to the framework established in recent decisions of the English Court of Appeal, the article seeks to forge a middle path between making anti-arbitration injunctions available on a discretionary, case management basis and prohibiting them in all cases. An approach that respects both the rights of arbitrators to determine their own jurisdiction and the rights of courts to protect parties from abuse of the arbitral process is advocated.